The irrigation of our plains - Thackrey, William Elwood (My University, 1896)
Introduction: Wherever the art of irrigation originated, among what people, or at whatever period of time, never was there at any other age, a more wide spread interest in this work than that felt today. This feeling has been growing until the interest now manifest in the United States gives promise, especially in that portion west of the Mississippi, of results that will exceed in extent any work yet accomplished by those eastern nations which have had centuries of experience.
Citation: Thackrey, William Elwood. The irrigation of our plains. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Irrigation; Plains; Art; Eastern nations; Theses; Manuscripts (documents)